2018
DOI: 10.1093/jxb/ery329
|View full text |Cite
|
Sign up to set email alerts
|

The WUSCHEL-related homeobox1 gene of cucumber regulates reproductive organ development

Abstract: The WUSCHEL-related homeobox1 (WOX1) transcription factor plays an important role in lateral growth of plant organs; however, the underlying mechanisms in the regulation of reproductive development are largely unknown. Cucumber (Cucumis sativus) has separate male and female flowers, facilitating the study of the role of WOX1 in stamen and carpel development. Here, we identified a mango fruit (mf) mutant in cucumber, which displayed multiple defects in flower growth as well as male and female sterility. Map-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 62 publications
2
27
0
Order By: Relevance
“…Expression pattern analysis of these CsWOX genes showed that a few of them were mainly expressed in specific organs, indicating that these genes may be involved in different development processes. For example, CsWOX1a mutation can lead to a mango fruit in cucumber 18 , which is consistent with that it was mainly enriched in fruit (Fig. 4A).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Expression pattern analysis of these CsWOX genes showed that a few of them were mainly expressed in specific organs, indicating that these genes may be involved in different development processes. For example, CsWOX1a mutation can lead to a mango fruit in cucumber 18 , which is consistent with that it was mainly enriched in fruit (Fig. 4A).…”
Section: Discussionsupporting
confidence: 88%
“…bers in cucumber, we performed BLASTp searches using the full-length sequences of 15 Arabidopsis AtWOX members and analyzed homeodomain using SMART software 11 . Consistent with previous study 18 , 11 putative CsWOX genes were identified in cucumber (Table 1). These genes encoded proteins ranging from 130 and 387AA (amino acids) while isoelectric point (pI) values ranging from 5.54 to 10.08, and the molecular weights from 14.66 to 43.64 kDa (Table 1).…”
Section: Identification and Phylogenetic Analysis Of Cswox Genes In Csupporting
confidence: 90%
See 2 more Smart Citations
“…1a ) 27 . We previously identified the cucumber mutant mango fruit ( mf ), which displays multiple flower growth defects as well as male and female sterility 28 . Map-based cloning revealed that a truncated protein lacking the conserved WUS box of WOX1-type transcriptional regulator (CsWOX1) was responsible for the mutant phenotype 28 .…”
Section: Resultsmentioning
confidence: 99%